Demokratie jetzt : der schwierige Weg zur deutschen Einheit : ein Zeitzeuge berichtet - Weigt, Gerhard 1938- (Evangelische Verlagsanstalt, 2015)
Gerhard Weigt gives a historical account of the movement Democracy Now (Demokratie Jetzt), describing its developments, the growth of the opposition, and the resistance in the DDR, based on accounts of the main actors in these events. Among the issues discussed are: the difficulties that the movement had in defining itself, the solidarity among its followers, the search for answers to existential societal questions and their increasing politicization, the relationship between the movement and the evangelical church, and the connections between Democracy Now and the Polish resistance of the 70s and 80s